TINGKAT PARTISIPASI PEREMPUAN PENGOLAH IKAN DALAM KELOMPOK USAHA BERSAMA DI CISOLOK, SUKABUMI - Yuliana, Ernik; Farida, Idha; Kusumawati, Enny (Jurnal Matematika Sains dan Teknologi, 2008)
Traditional fish processing industries in Cisolok Sukabumi is operated mainly by women organized in Kelompok Usaha Bersama (KUB). This study is aimed to explain the influence of women characteristics on their participatory level in KUB activities exploratory research design with survey method were used to collect data. Sample populations of this study were all fisherwomen who process fish product in KUB. Forty samples were chosen with random sampling and datacollected were analysed by using structural equation model (SEM). The results show that participation level of fisherwomen in KUB is still low. Fisherwomen characteristics have no significant influence to participation level in KUB activities. Structural model obtained is not fit between hypothetic model and sample data. Therefore the model can not be applied in the field. But at the other hand, KUB have to intensify means to give the skill extension for fisherwomen so that participatory rate will increase.